Hardness–structure Relationship in Nd:YAG Laser Irradiated High-purity Zinc. (2015) - Ali, D.; Butt, M.Z.; Aftab, M.; Bashir, F.
Abstract: Six specimens of 99.995% pure zinc were irradiated with a passive Q-switched pulsed Nd:YAG laser in a vacuum ̴ 10 -3 Torr. The specimens were irradiated with 50 to 100 laser shots with an increment of 10 shots. Williamson-Hall analysis of XRD patterns of un-irradiated and irradiated specimens was carried out to evaluate the structural parameters, namely crystallite size and micro-strain. Surface hardness of the specimens was measured using Vickers hardness tester. An inverse Hall-Petch relation for the surface hardness was observed in the 28–35 nm crystallite size range.